A new species of Erythrodiplax breeding in bromeliads in Costa Rica (Odonata: Libellulidae) - Haber, William A.; Wagner, David L.; Rosa, Carlos De La (Zootaxa, 2015)
We describe a new species, Erythrodiplax laselva (Libellulidae), that breeds in bromeliads and Cochliostema (Commelinaceae) in the eastern lowlands of Costa Rica. The closest known relative is thought to be E. castanea, widespread in Central and South America, and not E. bromeliicola, which is known to breed in bromeliads in Cuba and Jamaica. The male, female, genitalia, and larva are described and illustrated.